Tralopyril affects locomotor activity of zebrafish (Danio rerio) by impairing tail muscle tissue, the nervous system, and energy metabolism. (January 2022) - Chen, Xiangguang; Zheng, Junyue; Teng, Miaomiao; Zhang, Jie; Qian, Le; Duan, Manman; Cheng, Yi; Zhao, Wentian; Wang, Zhao; Wang, Chengju
Abstract: Tralopyril (TP), an antifouling biocide, is widely used to prevent heavy biofouling, and can have potential risks to aquatic organisms. In this study, the effect of TP on locomotor activity and related mechanisms were evaluated in zebrafish ( Danio rerio ) larvae. TP significantly reduced locomotor activity after 168 -h exposure. Adverse modifications in tail muscle tissue, the nervous system, and energy metabolism were also observed in larvae. TP caused thinning of the muscle bundle in the tail of larvae. In conjunction with the metabolomics results, changes in dopamine (DA) and acetylcholine (ACh), acetylcholinesterase (AChE) activity, and the expression of genes involved in neurodevelopment, indicate that TP may disrupt the nervous system in zebrafish larvae. The change in metabolites (e.g., glucose 6-phosphate, cis -Aconitic acid, acetoacetyl-CoA, coenzyme-A and 3-Oxohexanoyl-CoA) involved in carbohydrate and lipid metabolism indicates that TP may disrupt energy metabolism. TP exposure may inhibit the locomotor activity of zebrafish larvae by impairing tail muscle tissue, the nervous system, and energy metabolism. Graphical abstract: Image 1 Highlights: Tralopyril significantly inhibited the locomotor activity of zebrafish larvae. Tail muscle tissue of zebrafish larvae was impaired by tralopyril. Nervous system disruption was observed following exposure. Tralopyril disrupted carbohydrate and lipid metabolism in zebrafish larvae.